Comparison of swimmers` performances in the 98th Korea national sports festival - Choi, H.; Yang, M.-J. (World Congress of Performance Analysis of Sport XII, 2018)
Purpose: This study was to compare the swimming styles (such as numbers of strokes, breath, and timing) between superior and inferior players In Korea national swimming competition. Also, this study was to gather the Korean elite swimmer's performance and to prepare the feedback of analysed data to the swimmer. Methods: The subjects of this study were 100m and 200m advanced final player about all type of strokes (butterfly, back-stroke, breast-stroke and free style). All data gathered were divided by 2 groups (superior and inferior) and determined by independent t-test as statistical comparisons. Results: Firstly, there were no significant differences on the records of all swimming styles (butterfly, back-stroke. breast-stroke and free style) in 100m. However, there was a significant difference between 2 groups on the records of all swimming styles In 200m. especially after 100m. Secondly, there were no significant differences on the numbers of strokes of all swimming styles, but the numbers of strokes were fewer in the superior group than In the Inferior group. Thirdly, there were significant differences between 2 groups on the number of breaths, both 100m and 200m swimming. Conclusion: There were differences of performances between superior and Inferior group on the different distance such as 100m and 200m wtthin Korea national competition. However, for the considering of statistical comparison, there were no significant differences on the records of all swimming styles. Thus, those sorts of the analysis of swimming needs to be considered within the approaches of methods on the performance analysis rather than the consideration of simple records from the competition.